2018
DOI: 10.1080/07391102.2018.1465853
|View full text |Cite
|
Sign up to set email alerts
|

Novel coumarin derivatives as potent acetylcholinesterase inhibitors: insight into efficacy, mode and site of inhibition

Abstract: The inhibitory efficacy of two substituted coumarin derivatives on the activity of neurodegenerative enzyme acetylcholinesterase (AChE) was assessed in aqueous buffer as well as in the presence of human serum albumin (HSA) and compared against standard cholinergic AD drug, Donepezil (DON). The experimental data revealed the inhibition to be of non-competitive type with both the systems showing substantial inhibitory activity on AChE. In fact, one of the tested compounds Chromenyl Coumarate (CC) was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Additionally, van der Waals interactions were noted between compound 9 and residues ILE-275, ASP-276 and ILE-287. The involvement of the mentioned residues from the AS, AP, and PAS was confirmed to contribute stability to the complex between AChE and synthetic inhibitors such as coumarin-triazole-amino acid hybrids [ 55 ], tyrosol 1,2,3-triazole analogs [ 56 ], coumarin-3-carboxamide-N-morpholine hybrids [ 57 ], chromone derivatives [ 28 ], and chromenyl coumarate [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, van der Waals interactions were noted between compound 9 and residues ILE-275, ASP-276 and ILE-287. The involvement of the mentioned residues from the AS, AP, and PAS was confirmed to contribute stability to the complex between AChE and synthetic inhibitors such as coumarin-triazole-amino acid hybrids [ 55 ], tyrosol 1,2,3-triazole analogs [ 56 ], coumarin-3-carboxamide-N-morpholine hybrids [ 57 ], chromone derivatives [ 28 ], and chromenyl coumarate [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated IC­ 50 values indicate that both the chromones showed inhibitory efficiency akin to the reference drug DON. However, experiments on 2 coumarin derivatives reported elsewhere 59 revealed that replacement of the coumarin moiety with chromones results in a loss of inhibitory efficiency. Similar observation has already been reported in several SAR reviews and it is well-known that coumarin derivatives normally show better inhibition potency toward AChE activity in comparison with their chromone counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Mixed inhibition involves the binding of the inhibitor to both the native enzyme (E) and the enzyme–substrate (ES) complex following pathways A and B . Noncompetitive inhibition is a special kind of mixed inhibition observed for TAC and DON, where the inhibitor has equal affinity for both the pathways, resulting in similar magnitudes of α and α′. ,− In contrast, for ESE and HuPA, the values of α and α′ are different. Since the change in K m values (an increase of >95% in the case of both ESE and HuPA) are more significant than the change in V max values (a decrease of ∼25% for ESE and ∼15% for HuPA), the drugs have more affinity for the competitive pathway (path A ).…”
Section: Discussionmentioning
confidence: 99%